Perspectives of the Latin American Non-commercial Journal Publishing and South-South Collaboration before Commercial Business Models for Open Access - García, Arianna Becerril; López, Eduardo Aguado; García, Alejandro Macedo (Access: An International Journal of Nepal Library Association, 2023)
Currently, the polysemic concept of Open Access is broad enough to encompass different meanings, paths, principles and outcomes. In that spectrum, there are approaches more in favor of values such as equity, inclusion, democratization and participation. On the contrary, some others reproduce schemes of epistemic injustice and structural exclusion. In Latin America, scholarly communication has taken science as a public good. This model is collectively sustained and it provides universal benefit. Conversely, the Open Access business models offered by the commercial sector of scientific journals perpetuate exclusion, since they continue to be based on the paradigm of commodification of science. Both, access and knowledge generation are compromised when knowledge is privatized and commoditized. It is important to reflect on the evolution of the Open Access movement, its effects, the beneficiaries and the excluded. Latin America is proud to showcase an academy-owned publishing paradigm which is worthy to be understood, recognized and strengthened, and that is particularly beneficial for the Global South.